DNA cruciform arms nucleate through a correlated but asynchronous cooperative mechanism. - Matek, C; Ouldridge, T; Levy, A; Doye, J; Louis, A (American Chemical Society, 2012)
Inverted repeat (IR) sequences in DNA can form noncanonical cruciform structures to relieve torsional stress. We use Monte Carlo simulations of a recently developed coarse-grained model of DNA to demonstrate that the nucleation of a cruciform can proceed through a cooperative mechanism. First, a twist-induced denaturation bubble must diffuse so that its midpoint is near the center of symmetry of the IR sequence. Second, bubble fluctuations must be large enough to allow one of the arms to form a small number of hairpin bonds. Once the first arm is partially formed, the second arm can rapidly grow to a similar size. Because bubbles can twist back on themselves, they need considerably fewer bases to resolve torsional stress than the final cruciform state does. The initially stabilized cruciform therefore continues to grow, which typically proceeds synchronously, reminiscent of the S-type mechanism of cruciform formation. By using umbrella sampling techniques, we calculate, for different temperatures and superhelical densities, the free energy as a function of the number of bonds in each cruciform arm along the correlated but asynchronous nucleation pathways we observed in direct simulations.